Health utilities for participants in a population-based sample who meet eligibility criteria for lung cancer screening. (July 2022) - Ngo, Preston J.; Wade, Stephen; Vaneckova, Pavla; Behar Harpaz, Silvia; Caruana, Michael; Cressman, Sonya; Tammemagi, Martin; Karikios, Deme; Canfell, Karen; Weber, Marianne F
Highlights: Quality of life (QOL) is commonly considered in evaluations of health policies. Evaluations of screening can be biased by overestimating pre-screening QOL. Lung screening selects people with poorer QOL due to past smoking. QOL does not differ between proposed lung cancer screening selection criteria. Abstract: Introduction: Trial-based, risk-targeted lung cancer screening with low-dose computed tomography has been shown to reduce lung cancer mortality but implementation may depend on favourable cost-effectiveness evaluations where quality-adjusted life-years are a key metric. Baseline health utility values for a screening population at high risk of lung cancer are not likely to match age-specific population norms, and utilities derived from screening trials may not be representative of real-world screening populations. We estimated utility values for screening-eligible individuals in a population-based cohort study in Australia. Methods: Cancer-free participants aged 50–80 years in the New South Wales 45 and Up Study completed the 12-Item Short Form Survey (2010–2011). Mean SF-6D utility values were calculated for 19, 991 participants and compared across screening criteria defined by the US Preventive Services Task Force (USPSTF-2021/2013), NELSON trial eligibility, and the PLCOm2012 risk tool. Results: Mean SF-6D utility values were comparable across screening criteria: USPSTF-2021, 0.772 (95%CI, 0.768–0.776); USPSTF-2013, 0.764 (95%CI, 0.759–0.770); NELSON, 0.768 (95%CI, 0.763–0.774), and were each lower than among ineligible participants (0.810–0.814). While there was a decline in utilities with increasing risk of lung cancer as measured with the PLCOm2012 risk tool, mean utility values for those with ≥ 1.51% 6-year risk did not differ to other criteria (0.772, 95%CI, 0.767–0.776). Conclusion: Risk criteria are necessary for the efficiency of lung cancer screening programs, but they select populations with lower mean health utilities than population norms. We provide baseline values that can be used in cost-effectiveness evaluations of risk-targeted lung cancer screening.